Cataloging of audiovisual materials and other special materials a manual based on AACR 2 - Olson, Nancy B. (Minnesota Scholarly Pr., 1998)
Cataloging of Audiovisual Materials and Other Special Materials covers both cataloging and MARC coding and tagging for all kinds of special materials in all types of libraries. Types of material include videos, talking books, CD-ROMs, interactive multimedia, Internet resources, maps, all kinds of graphic materials, as well as toys, games, and kits.
Keywords: Anglo-American cataloguing rules -- Handbooks, manuals, etc; Anglo-American cataloguing rules 2; AACR-2; Audiovisuele middelen; Catalogage - Documents audiovisuels - Guides, manuels, etc; Catalogage - Non-livres - Guides, manuels, etc; Catalogage - Règles - Guides, manuels, etc; Titelbeschrijving; Cataloging of audio-visual materials -- United States -- Handbooks, manuals, etc; Cataloging of nonbook materials -- United States -- Handbooks, manuals, etc; Descriptive cataloging -- United States -- Rules -- Handbooks, manuals, etc; Katalogisierung; Richtlinie; Audiovisuelle Medien; USA; Einführung